Strengthening international fisheries law in an era of changing oceans - Caddell, Richard; Molenaar, Erik Jaap (Hart Publishing, 2019)
"This collection addresses the central question of how the current international framework for the regulation of fisheries may be strengthened in order to meet the challenges posed by changing fisheries and ocean conditions, in particular climate change. International fisheries law has developed significantly since the 1990s, through the adoption and establishment of international instruments and bodies at the global and regional levels. Global fish stocks nevertheless remain in a troubling state, and fisheries management authorities face a wide array of internal and external challenges, including operational constraints, providing effective management advice in the face of scientific uncertainty and non-compliance by States with their international obligations. This book examines these challenges and identifies options and pathways to strengthen international fisheries law. While it has a primarily legal focus, it also features significant contributions from specialists drawn from other disciplines, notably fisheries science, economics, policy and international relations, in order to provide a fuller context to the legal, policy and management issues raised. Rigorous and comprehensive in scope, this will be essential reading for lawyers and non-lawyers interested in international fisheries regulation in the context of profoundly changing ocean conditions"--